A Research on the Application of Blockchain Technology in Enterprise Finance - Shengping Zhu, Peipei Hu, Jiancan Zhang (Forest Chemicals Review, 2022)
Since its inception, blockchain technology has been effectively applied in many fields. Based on the theoretical assumption of rational cognition, this article intends to explore the application of blockchain technology in corporate finance. According to the characteristics of blockchain technology, this paper analyzes the impact mechanism of blockchain technology on enterprise finance from the aspects of accounting processing, accounting settlement and accounting information disclosure. Taking power grid companies as an example, build a distributed energy trading platform based on blockchain technology in the web environment and sort out a system covering trading platform design, financial process reengineering and the optimization of significant notes. Combined with the internal conditions and external environment of the application of blockchain technology in the enterprise finance, this paper puts forward the coping strategy, which is called the intellectualization of enterprise accounting. The accounting intelligent system based on blockchain technology can simplify accounting processing procedures and reduce the time and labor cost of accounting work. Its distributed encrypted storage can enhance the transparency of accounting data, improve the accuracy and objectivity of accounting information, and help companies implement efficient real-time audits and automatic audits. This research is the first to explore the application of blockchain technology in corporate finance, which has certain theoretical significance. However, the construction of this model is based on the power grid industry, which has certain limitations. Because many companies cannot store large amounts of basic data like the grid.